Relationship between isokinetic muscle strength and 100 meters finswimming time - Kunitson, V.; Port, K.; Pedak, K. (Journal of Human Sport & Exercise, 2015)
Finswimming is a sport where athlete uses one big monofin to produce propulsion. The purpose of this study was to describe relationship between isokinetic strength of different muscle groups and 100 meters finswimming time. Study questions was: what muscle groups have relationship with finswimming time. Methods: 17 international level monfin swimmers, 9 male (age 16,9 ±1,8 yrs., height 180,0 ± 10.0 cm., weight 76.0±6.9 kg) and 8 female finswimmers ( age 17,6 ±4,7 yrs., height 170,0 ± 10.0 cm., weight 68,6 ± 13,5 kg) performed 100 meters monofin surface swim and where also tested within a two days on isokinetic dynamometer (knee, hip and trunk extensors and flexors at angular speeds of 60°/sec ). Force data at angles from 0-90 degrees with 10 degree step were used for correlation. Results: There was a strong correlation (p<0.05) between swimming time and knee extensors (r=-0.82 at angle 50°), hip flexors (r=-0.70 at angle 10°) and trunk flexors (r =-0.77 at angle 20°) in male swimmers. Surprisingly, we did not find corresponding correlations among female finswimmers. Conclusion: Current study found relationship between strength of main muscle groups and swimming speed only in male swimmers. It is expected that strength plays a role in swimming time, but the lack of relationship in female swimmers suggests at the need to introduce a measure of swimming effectiveness instead of pure resultant time. The proposed hypothesis is further supported by the high level of competence among study participants (incl. multiple European champion, and several finalists).